Hypnotherapy as an alternative approach in reducing anxiety in the elderly - Annisa, Dona Fitri; Afdal, Afdal; Daharnis, Daharnis; Adlya, Soeci Izzati (Universitas Negeri Padang, 2019)
Old age is a natural process experienced by every human being who will reach old age. Old age is not a disease, but a normal process that cannot be avoided. In incomplete sentence old age many problems faced by the elderly both physical problems that have decreased and mental problems such as depression, stress and anxiety. Problems that occur in the elderly are important things that require attention and care. Hypnotherapy is one way that can be done in the elderly to reduce the problems that occur, especially regarding mental health such as anxiety. Hypnotherapy is a therapeutic method that uses hypnosis. Hypnotherapy is a direct response to the causes or roots of a problem, and what makes people enter hypnosis is the verbal suggestion. This paper tries to explain the concept of hypnotherapy and aspects related to hypnotherapy, which are aimed at reducing mental problems such as anxiety that occurs in the elderly.